American Consumer Acceptance of Satay Sauce as Affected by Different Peanut Grinding Methods, the Multi-step and One-step Processes, and Processing Times - Chompunut Sihsobhon; Penkwan Chompreeda; Vichai Haruthaithanasant; Thongchai Suwonsichon; Anna Resurrreccion (Agriculture and Natural Resources, 2008)
Satay is one of the ten most popular foods for US consumers visiting Thailand. American consumer acceptance for the convenience products resulted in the development of a process for ready to eat satay sauce. The objectives of this research were to determine the consumer acceptance and texture measurements of satay sauce as affected by peanut grinding methods, the one-step and multi-step process, and processing time, using consumer tests. Results showed that there were no significant differences in the overall acceptance from two replications (α>0.05), two processes (α>0.10) and two peanut grinding methods (α>0.10). There were significant differences in the overall acceptance (α<0.10) from three processing times because the effect of consumer liking scores of appearance and overall flavor were significant when increasing processing time. The significance of processing times and convenience of peanut grinding method and suitability of process indicated that satay sauce should be prepared using a one-step process and processed for 45 min, and peanuts should be ground in a peanut butter machine.